Ownership structures influence on audit fee - Puat Nelson, Sherliza; Mohamed-Rusdi, Nurul Farha (Emerald Group of Publishing Ltd, 2015)
Purpose : The purpose of this study is to investigate the association between corporate ownership structures and audit fees paid to external auditors by Malaysian companies listed on Bursa Malaysia. This study focuses on the extent of the auditor’s reliance on the client’s internal control inasmuch as the corporate ownership structures are varied, and, ultimately, affect the audit fees. Design/Methodology : This study applies the agency theory in formulating three hypotheses that guide the results analysis. By employing a multi regression model for a sample of 345 Malaysian companies listed on Bursa Malaysia, this study examines the relationship of ownership structure, namely, managerial ownership, foreign ownership and government ownership with audit fees using data for 2010. Findings : The results show a significant positive relationship between audit fees and firms with larger foreign ownership and government ownership but no significant relationship with firms with higher managerial ownership. This study contributes recent evidence concerning the relationship between corporate ownership structure and audit fees. Practical implications : The regulator may consider ownership structure on the standards or regulation setting in order to be practical and operationalized in line with the impact associated with different ownership structures. The practitioners may also design appropriate methodologies and procedures for the different ownership structures for high quality service and to standardize the risk mitigation process. Social implications : The ownership structures have different influences on the audit fees, as well as complexity of the firms and their profitability. Originality : The study looks upon certain percentages of ownership structures, and how they affects audit fees, firms complexity and profitability.